Проблеми та перспективи розвитку виробництва мила в умовах конкурентного середовища підприємств олійно-жирової галузі - Попов, Микола Олексійович; Дьякова, Наталія Миколаївна; Севастьянова, Ніна Дмитрівна (НТУ "ХПІ", 2017)
Розглянуто місце миловареного сектору в олійно-жировій галузі зокрема та промисловості України в цілому. Проаналізовано динаміку виробництва мила за його видами. Визначено структуру виробництва миловареної продукції на конкурентному ринку України. Ідентифіковано основні проблеми, що стримують розвиток виробництва мила у сучасних умовах господарювання вітчизняних спеціалізованих підприємств. Запропоновано потенційні заходи щодо перспектив розвитку операторів цільового ринку як на вітчизняному, так і світовому.

The place of the soap sector in the oil and fat industry in particular and the industry of Ukraine as a whole is considered. The dynamics of production of soap by its types is analyzed. The structure of production of soap products in the competitive market of Ukraine is determined. Attention is focused on the formation of domestic operators of the market for soap products. The analysis of volumes of soap production in the context of specialized enterprises of Ukraine in 2011 and 2014 is given. Identified the main problems that hinder the development of soap production in modern conditions of management of domestic specialized enterprises. Potential measures are proposed for the development of operators of the target market, both domestic and global, from a technical and economic point of view.
Problems and prospects of soap production development in the competitive environment of oil and fat industry enterprises
Keywords: спеціалізовані підприємства; миловарний комплекс; ринок; іноваційні заходи; problems of enterprise development